Dog Demography And Level Of Knowledge Against Rabies In Positive And Negative Case Of Rabies Areas In Mendoyo-Jembrana, Bali, Indonesia (DEMOGRAFI ANJING DAN TINGKAT PENGETAHUAN MASYARAKAT TERHADAP RABIES DI DAERAH DENGAN KASUS RABIES POSITIF DAN NEGATIF - Agustina, Kadek Karang; Cahyani, Putu Sasmitha Devi; Suardana, Ida Bagus Kade (Jurnal Veteriner, 2018)
This research aims were to compare the demography of dogs and knowledge profile of dog owners against rabies in Mendoyo Sub-District, Jembarana Bali. This research used observational method, conducted from May to June 2016 in Mendoyo sub-district of Jembrana. Two Banjars were selected by the rabies case report in dogs (YehEmbangKangin village) and two other without case (MendoyoDanginTukad village). The data collected by interviewing the community and direct assessment of free-roaming dogs in the areas. A total of 200 household samples were taken, 50 respondents of each sampling area. This research resulted that the ratio of man-dog in Mendoyo was 4.5:1 and the ratio of male and female dogs was 1.8:1. As many as 64.8% of dog’s age were more than 12 month old, 28% were 4 to 12 month old and 8% were less than 4 month old. In the sampling areas, 19.4% of dogs were sterilized, which were 91.18% males and 8.82% females. Coverage of rabies vaccination in owned dogs was 82.3%. Dog’s petting method by people in Mendoyo was 69.71% free-roaming while 30.29% tied or caged. On free-roaming dog assessment, this study found 52 free-roaming dogs on the streets, 65.38% males and 34.62% females, only 30.8% of those used vaccination collar marker, Based on the body condition score, 76.9% of free-roaming dogs have good conditions. Of the total 200 households surveyed, there was a high level of knowledge about the danger of rabies and the importance of vaccination, but only a few people (<35%) received consulting about rabies, understood how to prevent rabies infection and the regulations about dog petting management. In positive area, we found there are still many people who have the habit of disposing dog. We conclude that there is needed to improve knowledge and attitude of the community about the prevention and risk factor of rabies.
Keywords: demography, dog, knowledge level, rabies.